Instrumental motivation appears tobe more effective and more powerful in facilitating second language learning in comparison with integrative motivation - Khair, Tahia (BRAC University, 2010)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2013.